Reading picture books with children : how to shake up storytime and get kids talking about what they see - Lambert, Megan Dowd (Charlesbridge, 2015)
Traditional storytime often offers a passive experience for kids, but the Whole Book approach asks the youngest of readers to ponder all aspects of a picture book and to use their critical thinking skills. Using classic examples, Megan asks kids to think about why the trim size of Ludwig Bemelman's Madeline is so generous, or why the typeset in David Wiesner's Caldecott winner, The Three Pigs, appears to twist around the page, or why books like Chris Van Allsburg's The Polar Express and Eric Carle's The Very Hungry Caterpillar are printed landscape instead of portrait. The discussions that result from this shared reading style aims to inspire adults to make children's responses to text, art, and design an essential part of storytime.